Screening of Extended-Spectrum β-Lactamases (ESBL)-producing Klebsiella pneumoniae with ChromID ESBL Media - Emy Noerwidayati; Andaru Dahesihdewi; Osman Sianipar (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Klepsiella pneumoniae, one of clinical isolates, is frequently found causative agent of hospital acquired infection. Currently, K. pneumoniae is found as extended-Spectrum β-lactamases (ESBL) producer, allowing it to become multidrugresistant. A clinical laboratory with limited facility needs a valid, reliable, inexpensive and simple laboratory test to control its infection and antimicrobial-resistancy. The aim of this study is to evaluate the diagnostic performance of a ESBL media to detect ESBL-producing K. pneumoniae.METHODS: An independent and blind comparative study of ChromID ESBL media and Double Disc Synergy Test (DDST) was conducted for detecting the clinical isolate of ESBL-producing K. pneumoniae. Clinical isolates of K. pneumoniae collected from the Clinical Laboratory of Dr. Sardjito Hospital were isolated.RESULTS: There were 103 clinical isolates of K. pneumoniae, which were isolated from urine, pus, blood, stool, cerebrospinal fluid, sputum, drain liquid, nasal sinus liquid, gastric wash, bronchi liquid, injury liquid and nasal swab. The number of true positive, true negative, false positive and false negative results were 74, 18, 9 and 2, respectively. Meanwhile, the sensitivity, specificity, positive predictive value, negative predictive value, likelihood ratio for positive result and likelihood ratio for negative result of the new ESBL media were 97.4%, 66.7%, 89.2%, 90%, 2.9 and 0.03, respectively.CONCLUSION: Since the new ESBL media and DDST results were similar, so the new ESBL media could be used for screening patients with clinical presentation that indicating a high suspicious of ESBL-producing bacteria.KEYWORDS: K. pneumoniae, ChromID ESBL, DDST, ESBL, sensitivity